SOLUSI KEMACETAN JALAN SILIWANGI DI KOTA SEMARANG - Sugiharto, Arsono; Hendarto, R. Mulyo (Diponegoro Journal of Economics, 2013)
The purpose of this research is to describe the traffic congestion at Siliwangi Street in Semarang and to analyze the traffic congestion’s problem solving policy’s towards Siliwangi Street in Semarang. Traffic congestion is one of the negative impact of growing and development city. The uncontrollable increasingly private vehicle users every years in the city become the main cause of the traffic congestion happen.This research is using Analytival Hierarchy Process (AHP) as its method. This method is used to analyze 14 alternatives policy’s of traffic congestion that given by the Key Informans who had been interviewed before those alternatives are divided into three aspects, they are Economic Aspect, Social-Culture Aspect, and Institutional Aspect. All alternatives policy’s will be analyze by 3 kinds of respondents, they are Key Informans, citizens around the Siliwangi Street and the user of Siliwangi Street.The result of this research indicated that according to the whole alternatives of every aspects by each respondent to choose policy in order to reduce the traffic congestion with optimalizing motorized vehicle Progressive Tax with inconsistency ratio about ≤ 0,1, it means that this analysis is consistent and could be accepted to become a policy. Optimalizing motorized vehicle Progressive Tax is the highest priority policy than the other policies. Motorized vehicle Progressive Tax has the main purpose to reduce the number of vehicle in the streets then it can make the street capacity seems wider. Vehicle Progressive Tax can effectively reduce the traffic congestion in the Siliwangi street especially if the implementation doing in the right way and with one condition that the people do not do cheating to the government.